Analysis of Factors Affecting Essentials Oil Export to United States in Central Java Province, 1990-2019 - Dwi Joko Siswanto; Rafida Rafsanjani; Ickhsanto Wahyudi; Tantri Yanuar Rahmat Syah (Syntax Corporation Indonesia, 2022)
This study aims to determine the factors that influence essential oil exports to the United States from Central Java Province. The independent variables contained in this study are the export price of essential oil in Central Java Province, the exchange rate, the GDP importing country (U.S.). In contrast, the dependent variable is the volume of essential oil exports in Central Java Province. This type of research is a descriptive study with a quantitative approach. The data used in this study are annual time series data from 1990-2019 with 30 data. This research is conduct through the official website to obtain research data, including the Central Bureau of Statistics, the Ministry of Trade of Indonesia, Bank Indonesia, and various other sources. Data analysis in this study using multiple linear regression analysis. In the simultaneous test results (F-test), the variable export price of essential oil in Central Java Province, exchange rate, GDP Importing Country (U.S.) simultaneously has a significant effect on the volume of essential oil exports in Central Java Province. In the partial test results (t-test), the variable GDP importing country (U.S.) partially affects the dependent variable. Meanwhile, the export price of essential oil in Central Java province and variable the partial test of the exchange rate has no significant impact on the dependent variable.